2023
DOI: 10.1007/s00259-023-06399-7
|View full text |Cite
|
Sign up to set email alerts
|

Multi-task deep learning-based radiomic nomogram for prognostic prediction in locoregionally advanced nasopharyngeal carcinoma

Bingxin Gu,
Mingyuan Meng,
Mingzhen Xu
et al.

Abstract: Purpose Prognostic prediction is crucial to guide individual treatment for locoregionally advanced nasopharyngeal carcinoma (LA-NPC) patients. Recently, multi-task deep learning was explored for joint prognostic prediction and tumor segmentation in various cancers, resulting in promising performance. This study aims to evaluate the clinical value of multi-task deep learning for prognostic prediction in LA-NPC patients. Methods A total of 886 LA-NPC patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Recent development in PET radiomics studies have shown increasing clinical value of the high order image features in predicting the chemoradiotherapy response of cancer patients [49,50]. Besides, artificial intelligence (AI) algorithms, such as neural network and support vector machine, heavily rely on the high order features of clinical image as well [51][52][53][54]. The results of our study also partially impied the impact of scan duration and tracer dose on treatment assessment and AI based analysis when using PET/MR brain imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Recent development in PET radiomics studies have shown increasing clinical value of the high order image features in predicting the chemoradiotherapy response of cancer patients [49,50]. Besides, artificial intelligence (AI) algorithms, such as neural network and support vector machine, heavily rely on the high order features of clinical image as well [51][52][53][54]. The results of our study also partially impied the impact of scan duration and tracer dose on treatment assessment and AI based analysis when using PET/MR brain imaging.…”
Section: Discussionmentioning
confidence: 99%